Evaluation and Comparison of Anticonvulsant Activity of Telmisartan and Olmesartan in Experimentally Induced Animal Models of Epilepsy - V H, Pushpa (J Clin Diagn Res, 2014)
Background: Epilepsy is one common neurological disorder requiring newer targets and newer drugs for its efficient management. In the recent days brain renin angiotensin system has gained immense importance because of its involvement in seizure regulation. Objective: To evaluate and compare antiepileptic activity of different doses olmesartan and telmisartan on MES and PTZ induced seizure models. Materials and Methods: Swiss albino mice weighing around 25-30g of either sex were divided into 6 groups: Control ( Distilled Water- 10ml/kg), Standard – Sodium valproate (40mg/kg), O1 – Olmesartan (2.5mg/kg), O2 – Olmesartan (5mg/kg), T1 - Telmisartan (5mg/kg), T2 – Telmisartan (10mg/kg). After 1hour of administration of control , test and standard drugs (orally), convulsions were induced by administering PTZ (70mg/kg – i.p.) in PTZ model. Seizure latency was the parameter recorded. In MES model, suppression of tonic hind limb extension was taken as measure of efficacy. Result: The results were analysed by one-way-ANOVA followed by Bonferroni’s multiple comparison test. In MES test, dose dependently olmesartan and telmisartan significantly reduced the duration of tonic hindlimb extension in comparison to control (p<0.05). T2 – 9 + 0.89secs significantly reduced the tonic hind limb extension compared to other test groups (p<0.05). The percentage inhibition of seizure was T2-44.3%, O2-28.2%, T1-17.5%, O1- 12.3% respectively. In PTZ test, dose dependently olmesartan and telmisartan produced significant increase in seizure latency (p<0.05). T2 - 206.6+9.83secs significantly increased seizure latency compared to other test groups (p<0.05). Percentage protection from seizure is T2-52.6%, O2- 45.13%, T1- 37.5%, O1- 38.4% respectively. Conclusion: AT1 receptor antagonist, telmisartan and olmesartan in a dose dependent manner showed increase in antiepileptic activity. Temisartan at higher dose produced significant antiepileptic activity in comparison to olmesartan.